Hemadri - Renowned Commentator of Ayurvedarasayana Commentary on Ashtangahridayam - Vishwavasu Gaur; Vaidya Banwari Lal Gaur (Journal of Ayurveda, 2022)
Background: Hemadri, the prominent minister of King Mahadeva and Ramdeva of Devagiri, Maharashtra, was very eminent scholar belonging to the 13th–14th century. He has written many scholarly books and Ayurvedarasayana commentary on Ashtangahridayam is considered his masterpiece. Objective: The objective of this study is to enlighten the contribution of Acharya Hemadri in the field of Ayurveda. Data Source: The books, i.e., Ayurvedarasayana commentary on Ashtangahridayam, Life of Hemadri, Vagbhatavimarshah, KashyapasamhitaUpodghata, etc., have been reviewed. Review Methods: Thorough study of data source followed by critical and rational analysis of the life and works of Hemadri. Results and Conclusion: The commentary is incomplete, but it is written with a practical approach and the author has amended the order of chapters and has organized it more systematically. The remarkable features of his commentary are the reorganization of Nidanasthana and Chikitsitasthana in such a way that after each chapter of Nidanasthana the corresponding Chikitsita is explained.